Legal Protection and Empowerment of Traditional Fishermen in Tasikagung Village, Rembang Regency - Bayu Nito Ilham Satria; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2025)
The purpose of this study was to analyse (1) legal protection and empowerment of the rights of traditional fishermen in Tasikagung Village based on Law No. 32 of 2014 and (2) obstacles in efforts to provide legal protection and empowerment for traditional fishermen in Tasikagung Village. The study utilizes normative legal methods, employing a legislative and conceptual approach, and draws support from relevant literature. The results of the study indicate that the protection and empowerment of traditional fishermen in Tasikagung Village are crucial. However, the implementation of Law No. 32 of 2014 encounters challenges, including weak law enforcement, overlapping regulations, and insufficient socialization. To address these challenges, an effective strategy is necessary, involving increased supervision, bureaucratic simplification, and improved access to capital and technology, along with collaboration among the government, fishermen's organizations, and the private sector.